The Effect of Using the iPusnas App (Digital Library) on Literacy Skills and Learning Outcomes of Year 11 Economics Students at SMA Negeri 8 Kupang - Yosinta Hartati Luhur; Ari Data; Markus U. K. Yewang (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2026)
This investigation was precipitated by the deficient literacy competencies and suboptimal academic attainment observed among eleventh-grade students in Economics at SMA Negeri 8 Kupang. The study sought to ascertain the magnitude of influence exerted by the utilization of the iPusnas application on students' literacy proficiencies and scholastic outcomes in Economics at the aforementioned institution. The inquiry employed a quantitative paradigm underpinned by a survey-based design. The aggregate population encompassed 105 eleventh-grade students, from which a cohort of 83 respondents was delineated through proportional random sampling. Empirical data were garnered via systematic observation, structured questionnaire dissemination, and documentary corroboration. Analytical procedures were executed through Structural Equation Modeling Partial Least Squares (SEM-PLS), operationalized through SmartPLS 4 software, encompassing the rigorous appraisal of both the outer and inner measurement constructs. The findings substantiated that the deployment of the iPusnas application exerted a positive and statistically consequential influence on students' literacy competencies. Concomitantly, literacy proficiency was found to bear a positive and significant bearing on academic attainment. Moreover, the utilization of the iPusnas application was independently corroborated to yield a positive and significant bearing on scholastic outcomes. Collectively, these findings affirm that the integration of the iPusnas application constitutes a demonstrably efficacious intervention in augmenting both literacy competencies and academic performance in the domain of Economics.